Investigation on liquid crystal based tuning elements for tunable diode laser - Wang, Pin (2010)
Tunable lasers have a lot of applications ranging from light sources for fiber optic telecommunication system to broadband system. One popular approach to the design of tunable laser is the external cavity laser (ECL). The review of current tunable ECLs suggests it is desired to have electronically tunable ECLs that are simple in configuration, easy in fabrication and assembly. Also, employing liquid crystals (LCs) as tuning elements for the tunable ECL permits low voltage tuning of the lasing wavelength. In this context, investigation into LC based tuning elements with novel concepts for tunable ECL application has good relevance and significance.